Impoliteness Strategy for Cyberbullying in Indonesian on Instagram Social Media - Subyantoro,; Suseno,; Zuliyanti,; Putri, Shalina Fadilya Diani (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Power relations in the use of language on social media can give rise to language deviation in the form of hate speech or cyberbulling. This research aims to explain how impolite strategies in the form of cyberbullying speech in Indonesian on social media have the potential to violate the Electronic Information and Transactions (ITE) Law. This research uses a content analysis method. The researchers utilized a scrutinizing approach through the Scrutinize, Be Free, Get Involved, Talk (Simak Bebas Libat Cakap/SBLC) technique as a basic stage and a note-taking technique was applied as an advanced technique. This research data is in the form of fragments of netizen comments and captions on Ayu Ting-Ting's haters account on Instagram which contains cyberbullying hate speech conveyed by netizens on Instagram. The research results show that there are two types of impoliteness strategy, namely positive impoliteness and negative impoliteness. Positive impoliteness was found in nineteen comments with a percentage of 38%, while negative impoliteness was found the most with thirty-one comments with a percentage of 62%. Negative impoliteness strategy is higher because there are many characteristics of negative impoliteness strategy, including attacking or threating negative face of the interlocutor, impoliteness by scaring the interlocutor, impoliteness by ridiculing or mocking, impoliteness by warning the interlocutor. The conclusion of this research is that more negative impoliteness strategy is used when using Indonesian on social media. This tendency is the cause of the increasingly widespread cyberbullying that occurs in the use of social media today.